Modern approaches to the prevention of actinobacillus pleuropneumonia in pigs - Nikolay V. Pimenov; Alexandra A. Shashkova; Alexander A. Kruglov (RUDN Journal of Agronomy and Animal Industries)
Information about the current situation with actinobacillus pleuropneumonia (APP) in the Russian Federation is quite limited, which makes it difficult to assess the effectiveness of current preventive measures and develop new strategies. The diversity and effectiveness of vaccines play an important role. The main aim of the study is a scientific review of modern approaches to the APP prevention in pigs and prospects for the development of a vaccine that provides comprehensive protection against all known serotypes of this pathogen. The methods of systematization, critical analysis, and problem review are used. Over the years, various vaccines have been developed to combat this disease. Inactivated bacterial vaccines provide a strong immune response, but their effectiveness may vary. Based on the outer membrane proteins and three Apx toxoids, subunit vaccines are able to provide protection regardless of the APP serotype. DNA vaccines show promising results but require further research. Live attenuated vaccines contain weakened microorganisms and stimulate strong immunity, but their use also has its own difficulties. Despite all the successes achieved, at the moment there is no reliable and commercially profitable vaccine that would protect against all known serotypes of A . pleuropneumoniae and prevent the carriage and transmission of the disease. The problem of specific prevention of APP requires an integrated approach, including further scientific research, the development of new technologies and innovative methods of vaccination. Scientists increasingly focus on research in the field of oral and nasal vaccines. One of the important advantages is cost-effectiveness and safety during production, as well as convenience and safety of vaccine application. Oral and nasal vaccines can significantly simplify the immunization process, especially in the context of mass vaccination. Studies of vaccines based on external membrane vesicles and transgenic plants show promising results.